Expression of opsin genes early in ocular development of humans and mice. - Tarttelin, E; Bellingham, J; Bibb, L; Foster, R; Hankins, M; Gregory-Evans, K; Gregory-Evans, C; Wells, D; Lucas, R (2003)
We have compared the onsets of expression of the classical visual opsins with those of the non-rod, non-cone opsins in foetal and post-natal eye tissue from mice and humans. Mouse Rgr-opsin, peropsin, encephalopsin and melanopsin are all expressed in foetal development by E11.5, unlike the murine rod and cone opsins that exhibit post-natal expression, e.g. P1 for ultraviolet cone opsin and P5 for rod opsin. Human non-rod, non-cone opsins are also all expressed early, by 8.6 weeks post-conception. The implications of these observations are discussed with regard to the possible functions of these opsins at early stages of ocular development.